TERAPI BERMAIN TERHADAP TINGKAT KECEMASAN ANAK PRASEKOLAH YANG MENGALAMI HOSPITALISASI : A LITERATURE REVIEW - Daniel, Daniel (ProNers, 2021)
ABSTRACTBackground : Hospitalization can cause anxiety in some children. The level of anxiety due to hospitalization in most preschool children is severe anxiety. Play therapy is a therapy that can reduce the anxiety level of preschool children. Objectives: To identify the literature on the effect of play therapy on the anxiety of preschool children who experienced hospitalization and to determine the decrease in anxiety levels before and after being given play therapy. Methods: This is aresearch  literature review, the article comes from Google scholar with 13,702 searches, Garuda portal 4 searches and Researchgate with 90 searches, a total of 13,796 searches. Then it wasscreened and read according to the inclusion criteria, 13,788 articles were issued and then 8 main articles were obtained. Results : Plasticine therapy, coloring pictures, lego, origami and super bubbles got 0.000 results so it is very effective in reducing children's anxiety levels. In addition, constructive play therapy with a result of 0.0001 provides very effective results for children's anxiety, storytelling therapy showed a significant effect on children's anxiety levels with a result of 0.003 and puzzle play therapy got a result of 0.005 indicating that puzzle playing therapy had an effect on decreasing the level of anxiety. child anxiety. Conclusion: Play therapy such as plasticine therapy, coloring pictures, lego, origami, bubbles, constructive, storytelling and puzzles are very effective in reducing the anxiety level of children who are undergoing hospitalization.Keywords : Anxiety, Hospitalization, Play therapy, Preschool children.  ABSTRAK  Latar belakang : Hospitalisasi dapat menimbulkan kecemasan pada sebagian anak. Tingkat kecemasan  akibat hospitalisasi pada sebagian besar anak prasekolah adalah kecemasan berat . Terapi bermain adalah terapi yang dapat menurunkan tingkat kecemasan anak prasekolah. Tujuan : Mengidentifikasi literatur mengenai pengaruh terapi bermain terhadap kecemasan anak prasekolah yang mengalami hospitalisasi dan mengetahui penurunan pada tingkat kecemasan sebelum dan sesudah diberikan terapi bermain. Metode : Jenis penelitian yang digunakan adalah literatur riview, artikel jurnal berasal dari Google scholar dengan hasil 13.702 penelusuran, portal Garuda 4 penelusuran dan Researchgate dengan hasil 90 penelusuran, total seluruhnya 13.796 penelusuran. Kemudian discreening dan dibaca sesuai dengan kriteria inklusi, artikel yang dikeluarkan sebanyak 13.788 dan di dapatkan 8 artikel utama. Hasil : Terapi plastisin, mewarnai gambar, lego, origami dan gelembung super mendapatkan hasil 0,000 sehingga sangat efektif menurunkan tingkat kecemasan anak. Selain itu terapi bermain konstruktif dengan hasil 0,0001 memberikan hasil yang sangat efektif untuk kecemasan anak, terapi bercerita menunjukkan adanya efek signifikan pada tingkat kecemasan anak dengan hasil 0,003 dan terapi bermain puzzle mendapatkan hasil 0,005 menunjukkan bahwa terapi bermain puzzle memberikan pengaruh terhadap penurunan tingkat kecemasan anak. Kesimpulan : Terapi bermain seperti terapi plastisin, mewarnai gambar, lego, origami, gelembung, konstruktif, bercerita dan puzzle  efektif untuk menurunkan tingkat kecemasan anak yang sedang mengalami hospitalisasi.Kata Kunci : Anak prasekolah, Hospitalisasi, Kecemasan, Terapi bermain